Answer:
ustee
Step-by-step explanation:
The other ones don't make sense if you insert them into that sentence
Answer:
Your answer would be D
Step-by-step explanation:
First we are going to find the common denominator of both fractions. To do that, we are going to multiply their denominators:
![(1+sin \alpha )(1-sin \alpha )=1-sin^2 \alpha](https://tex.z-dn.net/?f=%281%2Bsin%20%5Calpha%20%29%281-sin%20%5Calpha%20%29%3D1-sin%5E2%20%5Calpha%20)
Now we can rewrite our expression using the common denominator:
![\frac{1-sin \alpha }{1-sin^2 \alpha } + \frac{1+sin \alpha }{1-sin^2 \alpha} = \frac{2}{1-sin^2 \alpha}](https://tex.z-dn.net/?f=%5Cfrac%7B1-sin%20%5Calpha%20%7D%7B1-sin%5E2%20%5Calpha%20%7D%20%2B%20%5Cfrac%7B1%2Bsin%20%5Calpha%20%7D%7B1-sin%5E2%20%5Calpha%7D%20%3D%20%5Cfrac%7B2%7D%7B1-sin%5E2%20%5Calpha%7D%20)
Finally, we can use the trig identities:
![1-sin^2 \alpha =cos^2 \alpha](https://tex.z-dn.net/?f=1-sin%5E2%20%5Calpha%20%3Dcos%5E2%20%5Calpha%20)
and
![sec \alpha = \frac{1}{cos \alpha }](https://tex.z-dn.net/?f=sec%20%5Calpha%20%3D%20%5Cfrac%7B1%7D%7Bcos%20%5Calpha%20%7D%20)
to simplify our trig expression:
We can conclude that the correct answer is the fourth one.
Answer:
1) m = h - w/8
Subtract h from both sides.
m - h = -w/8
Subtract m from both sides.
-h = -m - w/8
Divide all terms by -1.
h = m + w/8.
2) m = h - w/8
Get rid of the denominator 8 by multiplying 8/1 to all terms.
8m = 8h - w
Add w on both sides and subtract 8m from both sides.
w = 8h - 8m
3) w = x + y/z
Get rid of the denominator z by multiplying it to all terms.
wz = xz + y
Subtract xz from both sides of the equation.
wz - xz = y OR y = wz - xz
4) w = x + y/z
Subtract x from both sides.
w - x = y/z
Get rid of the denominator by multiplying it to all terms.
wz - xz = y
Now factor the expression wz - xz.
z(w - x) = y
Divide both sides by w - x.
z = y / w - x
This is read as z equals to y divided by w minus x.
5) The area of a triangle is A = 1/2bh
First, get rid of the denominator by multiplying both sides by 2.
2A = bh
To find b, divide both sides by h.
2A/h = b
6) P = kt/v
Multiply both sides by v.
Pv = kt
Divide both sides by t.
Pv/t = k OR k = Pv/t.
Step-by-step explanation:
If solving for x you will first need to combine like terms. Then after getting the amount of numbers and amount of x numbers you will divide the x number from both. After doing that you would get X=-10